Translation initiation at a downstream AUG occurs with increased efficiency when the upstream AUG is located very close to the 5' cap. - Sedman, S A (J Virol, 1990)
The major late 16S mRNA species of simian virus 40 encodes both a 61-amino-acid protein, LP1, and the major virion protein, VP1. Although the initiation signal GCCAUGG is usually utilized at high efficiency, at least one-third of 40S ribosomal subunits bypass it when it is present on the major 16S mRNA of simian virus 40 (S. A. Sedman, P. J. Good, and J. E. Mertz, J. Virol. 63:3884-3893, 1989). The LP1 translation initiation codon is situated 10 bases from the 5' end of this mRNA. To determine whether the short length of the untranslated leader of this mRNA affects the efficiency of translation initiation at the LP1 initiation signal, monkey cells were transfected with plasmids which encode major late 16S-like mRNAs with 5' untranslated regions (UTRs) of 6 or 44 bases. Decreasing the length of the 5' UTR from 44 to 6 bases resulted in a 30% decrease in translation initiation at the LP1 AUG and a threefold increase in synthesis of VP1. When the VP1 open reading frame was replaced with the chloramphenicol acetyltransferase open reading frame, the reduction in 5' UTR length resulted in a 70% decrease in translation initiation at the LP1 AUG and a 30% increase in chloramphenicol acetyltransferase synthesis. Therefore, ribosomes bypass an AUG codon more efficiently when it is located very close to the 5' end of the mRNA. IMAGES: